Congenital utero-cervical and vaginal atresia: a rare case report - Sodhiya, Hemlata; Mukherjee, Shubhra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
A genesis of cervix is a very rare developmental anomaly. It may be associated with vaginal agenesis. The usual age of presentation is teenage, with symptoms like cyclical abdominal pain and failure to attain menarche. Earlier, hysterectomy used to be the only option for such girls. Recently reconstructive surgery is gaining popularity. This is a case report presenting an eighteen-year-old girl with classical symptoms, diagnosed with both cervical and vaginal atresia, and managed by reconstructive surgery (Singapore flap method). It was a single step surgery done by abdomino-perineal approach. The girl attained menses and has been symptom free at one year follow-up. The postoperative complications were minor and managed conservatively. A patient of cervical atresia should be given the option of a reconstructive procedure even in the presence of vaginal agenesis. Utero-cervical anastomosis has shown good results in several studies. However, the reproductive potential has to be assessed by long term follow up.